2016
DOI: 10.3390/ijerph13020200
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Support System-level Implementation of Health Promoting Schools: A Scoping Review

Abstract: Health promoting schools (HPS) is recognized globally as a multifaceted approach that can support health behaviours. There is increasing clarity around factors that influence HPS at a school level but limited synthesized knowledge on the broader system-level elements that may impact local implementation barriers and support uptake of a HPS approach. This study comprised a scoping review to identify, summarise and disseminate the range of research to support the uptake of a HPS approach across school systems. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Moreover, differences in characteristics related to the working group members, i.e., interpretation of the approach, the degree of practice-oriented thinking, the presence of one or more champions, and the dynamics within the working group, but also the differing degrees of influence of factors within the outer setting (i.e., support from the school board, national health-promoting trends, and the presence of and the capacity to collaborate with potential partners) resulted in different implementation processes. Other studies also found these contextual factors to facilitate and hinder implementation of school health-promoting interventions [33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, differences in characteristics related to the working group members, i.e., interpretation of the approach, the degree of practice-oriented thinking, the presence of one or more champions, and the dynamics within the working group, but also the differing degrees of influence of factors within the outer setting (i.e., support from the school board, national health-promoting trends, and the presence of and the capacity to collaborate with potential partners) resulted in different implementation processes. Other studies also found these contextual factors to facilitate and hinder implementation of school health-promoting interventions [33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Both investments were essential, but time-consuming. This is outweighed by the high potential of sustainability of the output of the intervention because of a high perceived ownership by the schools due to contextual fit [16,36]. Important lessons we have learned from implementing the KEIGAAF intervention are listed in Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, how school climate and adolescent health and well-being were identi ed and understood by the school community was an important contributory factor in the intervention implementation. A qualitative case study of a Canadian province-wide HPS initiative described that school health initiatives that are understood, supported, and perceived as consistent with the school culture by the school teachers and principals aid in successful implementation [23]. This gap in awareness and knowledge of programs among stakeholders has also been corroborated in past studies as barriers to sexual health and nutrition education and policy implementation within schools [24][25].…”
Section: Discussionmentioning
confidence: 90%
“…Capacity building is meant to make the involved settings responsible for, and more capable of, conducting and maintaining health promotion programs [9]. Capacity building can take place on different levels: individual level (e.g., training coaches), group level (e.g., improving the structure, functioning and learning environment of a project group), organizational level (e.g., integrating competences and skills in processes of schools or sports clubs), and the broader system level (e.g., developing multi-sectoral partnerships between different stakeholders and organizations in a community or rural region) [10][11][12]. It focuses on (community and municipal) structural development as a condition for social and organizational change as well as individual behavioral changes of the actors involved, either working with existing groups and organizations, or establishing new groups (e.g., in communities or schools).…”
Section: Introductionmentioning
confidence: 99%